To Be a Citizen : The Political Culture of the Early French Third Republic - Lehning, James R., 1947- (Book collections on Project MUSE., 2001)
France's Third Republic confronts historians and political scientists with what seems a paradox: it is at once France's most long-lived experiment with republicanism and a regime remembered primarily for chronic instability and spectacular scandal ...